(:unas) unassigned - Maitree Podisuk (My University, 2000)
The modified Newton method for solving systems of nonlinear equations is one of the Newton-like methods.In this paper, results that will ensure the existence and uniqueness solutions to a system of nonlinear equations will be given.A second order convergence result is established.
Keywords: null